KAJIAN FORTIFIKASI DAGING DAN KULIT BUAH NAGA MERAH (Hylocereus polyrhizus) TERHADAP MUTU MIKROBIOLOGI DAN ORGANOLEPTIK TAPAI KETAN PUTIH - Sari, Desy Ambar; Asmawati, Asmawati; Saputrayadi, Adi; Marianah, Marianah (Universitas Muhammadiyah Mataram, 2024)
White glutinous tapai is a fermented food product in which yeast is added in manufacturing. Red dragon fruit can be added to increase the nutritional value, taste and product diversification of processed white sticky rice tapai. Besides being rich in nutritional value, red dragon fruit also contains antioxidant compounds, natural food fiber and natural colouring compounds that display a purplish-red colour. This study aims to determine the effect of fortification of red dragon fruit meat and skin on fiber content and organoleptic quality of white sticky rice. This study was experimental, using a completely randomized design (CRD), with the fortification of red dragon fruit meat and skin in the production of white sticky rice tapai. The type of treatment: T1 = white glutinous rice without red dragon fruit (control), T2 = white glutinous rice + red dragon fruit pulp, T3 = white glutinous rice + (flesh and skin) of red dragon fruit, and T4 = white glutinous rice + red dragon fruit skin). Observational data were analyzed by analysis of variance (ANOVA) at a 5% significance level and follow-up test with HSD at the same significant level. The results of the analysis of the quantity of microorganisms in white sticky rice tapai yeast with fortification treatment of red dragon fruit flesh and skin showed that the sticky rice tapai contained 2.9x104 microbes in T1, 6.0x104 in T2, 7.1x104 in T3 and 4.0x104 in T4 and research results organoleptic properties of the colour, aroma, taste and texture score parameters. The best treatment preferred by the panellists was the T2 treatment (fortification of red dragon fruit pulp) with a fiber content of 4.13%, a pH value of 5.13, an aroma value score of 3.39 (slightly tapai flavour), a taste of 4.11 (liked it), texture 3.29 (slightly soft) with a purplish red appearance 3.86. The use of a mixture of dragon fruit, dragon fruit skin is able to produce the most suitable organoleptic assessment for white sticky rice compared to the use of dragon fruit skin from the results of organoleptic panelists and statistical tests. The use of dragon fruit in producing aroma, taste, and homogeneity are more preferred, while other parameters of color tend not to be affected. Total microbes, log 4.85, were the highest produced by fortification using dragon fruit skin. The use of dragon fruit flesh, which causes the sour taste is not strong and good color other treatments to be more acceptable to panelists.